Study on the Pattern of Antibiotic Use Including the Resistance Episodes in Bangladesh - Islam, M Shazzadul; Sikdar, KM Yasif Kayes; Hossain, ASM Monjur AL; Faroque, ABM (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Antibiotic resistance is currently one of the biggest challenges faced by the health professionals worldwide. Bacteria are becoming resistant to commonly used antibiotics and various factors have been identified that are responsible for the resistance. Factors like poor quality of antibiotic products, unethical marketing practices by pharmaceutical companies, irrational use of antibiotics by the physicians and patient incompliance are also common in Bangladesh. To carry out this study, firstly the extent of antibiotic resistance was evaluated by collecting clinical isolates from various diagnostic centers of Dhaka City and conducting antibiotic susceptibility test against commonly used antibiotics. The product quality was evaluated by collecting antibiotic products of different generics from various locations around Bangladesh and then performing drug content assay by HPLC method. Finally, to evaluate patient incompliance, a questionnaire-based survey was conducted on patients who took or had taken antibiotics recently and the collected data was analyzed statistically. The result of the investigation reveals that more than 80% of the collected Escherichia coli (E. coli) isolates were resistant to currently used antibiotics like, azithromycin, ciprofloxacin, amoxicillin, cefixime, cefuroxime, and moxifloxacin. Similar holds true for the collected Staphylococcus aureus (S. aureus) isolates. The product quality in terms of drug content and dissolution was good for most products irrespective of whether the manufacturer had a high market value or not. Patients survey revealed that 82% discontinued antibiotic therapy was due to carelessness (49%), a false sense of cure (36%) and high cost (15%). Dhaka Univ. J. Pharm. Sci. 18(2): 135-143, 2019 (December)